Spatio-temporal evolution of financial sustainability in Chinese public hospitals: evidence from provincial panel data (2010–2022) - Deng, Youyang (Frontiers in Public Health, 2025)
ObjectiveTo analyze the spatio-temporal evolution patterns of financial sustainability in Chinese public hospitals and identify key driving mechanisms.MethodsUsing balanced panel data from 31 Chinese provinces (2010–2022), we constructed a theory-grounded multidimensional financial sustainability evaluation framework and employed spatial econometric models and convergence testing.ResultsFinancial sustainability exhibited “fluctuating rise with intensifying regional differentiation” characteristics, evolving through three phases: steady improvement (2010–2015), rapid growth (2016–2019), and stable development (2020–2022). Spatially, a significant “high east-low west, strong south-weak north” pattern emerged, with global Moran's I of 0.347 indicating strong spatial autocorrelation. Club convergence analysis identified three groups with annual convergence speed of 1.8%. Government fiscal investment demonstrated a total effect of 0.401, including significant spatial spillover effects (0.089).ConclusionsPolicy transmission occurs through policy learning, talent mobility, and technological diffusion mechanisms. The findings validate spatial spillover and policy diffusion theories while providing scientific evidence for establishing adaptive financial guarantee mechanisms and offering valuable reference for healthcare financing in developing countries.